Investigating direct and indirect relationships between writing self‐efficacy, integrative processing and integrated understanding in a multiple‐document context - Bråten, Ivar; Haverkamp, Ymkje E.; Latini, Natalia; Strømsø, Helge I. (Journal of research in reading, 2025)
Background A common approach to assessing students' integrated understanding of multiple documents is to analyse their post‐reading written reports. This study investigated to what extent writing self‐efficacy directly and indirectly (via integrative processing) contributed to multiple‐document comprehension as assessed with an integrative writing task. Methods A sample of Norwegian university students (n = 67) read four documents on a controversial socio‐scientific issue and afterwards wrote reports on the issue without access to the documents. Multiple‐document comprehension was assessed in terms of how well the reports reflected an elaborated and integrated understanding of the four documents' content. A mediation analysis was conducted with students' working memory as a covariate, their confidence in their ability to write a text that integrated content from multiple source documents as a predictor, self‐reports of their integrative processing during reading as a mediator and multiple‐document comprehension as an outcome variable. Results There was an indirect relationship between multiple‐document‐based writing self‐efficacy and multiple‐document comprehension via integrative processing. However, no direct relationship between writing self‐efficacy and multiple‐document comprehension was found. The covariate of working memory uniquely adjusted students' multiple‐document comprehension. Conclusions In the context of written assessment of multiple‐document comprehension, multiple‐document‐based writing self‐efficacy and multiple‐document comprehension were indirectly related via integrative processing during reading. The results indicate that not only reading‐related but also writing‐related individual differences may come into play when multiple‐document comprehension is assessed with an integrative writing task. Highlights What is already known about this topic Students are often asked to document their understanding of a topic by writing from multiple documents. The written products are typically assumed to reflect their understanding of the content of the documents. Within the area of multiple‐document comprehension, the emphasis has been on reading‐related rather than writing‐related competencies when comprehension is assessed with a writing task. What this paper adds This paper brings writing self‐efficacy to the forefront in the written assessment of multiple‐document comprehension. A new writing self‐efficacy measure corresponding to the criterial task of writing from multiple documents is used to predict multiple‐document comprehension as assessed with an integrative writing task. This writing self‐efficacy measure predicts students' integrative processing during reading, which, in turn, predicts their multiple‐document comprehension. Implications for theory, policy or practice Writing self‐efficacy should be taken into consideration when using integrative writing tasks to assess multiple‐document comprehension. Self‐efficacy for writing from multiple documents should be targeted as part of integrated reading–writing instruction.